Service per Conception (S/C) dan Conception Rate (CR) Sapi Crossbreed (Persilangan Bos sondaicus dan Bos taurus) di Kecamatan Kupang Timur - Tarsisius Considus Tophianong; Frans Umbu Datta; Tri Utami; Nancy Foeh; Cynthia Gaina; Yohanes Simarmata; Putri Pandarangga; Yeremia Y. Sitompul; Herlina Umbu Deta (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2023)
Conception Rate (CR) and Service Conception (S/C) are two parameters for assessing the reproductive performance of cattle. This research was conducted to determine the value of S/C and CR in crossbreeding cattle in the working area of ​​the Public Health Center. The material used in this study was 72 crossbreed cattle aged 3-10 years. Semi-intensive rearing system with AI mating. The results the S/C in this study was 3.9 higher than the ideal standard of 1.6–2. The CR in this study was 58.6%. CR numbers are still relatively low from the ideal, namely 65 -75%.